Performance Evaluation of 3D Ultrasound Imaging Resolution of Single Transmitter/ Receiver with Coding Mask by Extracting Phase Information - Syaryadhi , Mohammad; Nakazawa, Eiko; Tagawa, Norio; Yang, Ming (Science and Technology - Recent Updates and Future Prospects Vol. 5, 2024)
Ultrasound imaging has been widely applied to medical diagnosis due to its superiority via non-ionizing radiation and its relatively low-cost system. Recently, structured ultrasound microscopy (SUM) has been proposed by using a single transmitter/receiver circuit while placing the coding mask. However, single transducers with a single time-series echo signal required several additional measurements compared to array transducers consisting of numerous elements to construct a 3D image. We are currently investigating the ultrasound imaging of a sensor that consists of a randomized encoding mask attached to a single lead zirconate titanate (PZT) oscillator for a puncture microscope application. The proposed model was conducted using a finite element method (FEM) simulator. To increase the number of measurements required by a single element system that affects its resolution, the transducer was rotated at various angles. The image was constructed by solving a linear equation of the image model, resulting in poor quality. In a previous work, the phase information was extracted from the echo signal to improve the image quality. This study proposes a strategy that integrates the weighted frequency subbands compound and a super-resolution technique to enhance the resolution in range and lateral direction. The image performance with different methods was also evaluated using the experimental data. The highest resolution image was achieved through a weighted frequency subband in the range direction. The results indicate that better image resolution and speckle suppression were obtained by applying the proposed method. In the future, experiments need to be carried out with a real single-coding mask transducer system to confirm the current results with a qualitative and quantitative evaluation using the proposed method.